Agency Theory and Executive Compensation: The Case of Chinese State‐Owned Enterprises - Mengistae, Taye; Colin Xu, Lixin (Journal of Labor Economics, 2004)
This article examines the extent to which agency theory may explain chief executive officer (CEO) compensation in Chinese state‐owned enterprises during the 1980s. We find support for the agency theory: CEO pay sensitivity decreases with the variance of performance. Moreover, the performance sensitivity of CEO pay increases with the marginal return to executive action. While the elasticity of pay to sales is slightly smaller than that found for conventional firms in the West generally, our estimate of the semielasticity of pay with respect to profitability is comparable with estimates for regulated industries in the United States.